Hello there!
3x - y = 3
-x + y = 3
We need to solve 3x - y = 3 for y
Let start by adding -3x to both sides
3x - y = 3
3x - 3x - y = 3 - 3x
-y = 3 - 3x
We cannot leave the variable with a negative sign. We must multiply both sides by -1
-y * -1= (3 - 3x)-1
y = 3x - 3
Substitute 3x -3 for y in -x+y=3
-x + y = 3
-x + 3x - 3 = 3
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6/2
x = 3
Now substitute 3 for x in y=3x -3
y = 3x - 3
y = 3(3) - 3
y= 9 - 3
y= 6
Thus,
The answer is x=3 and y=6
It is always my pleasure to help students like you :)
As always, I am here to help!
Answer: 76.28 approximately 76
Step-by-step explanation:
Ryan bought fishing gear for 51.50, 14.99 and 5.79.
Total fishing gear bought will be the addition of the 3 fishing gear.
51.50 + 14.99 + 5.79= 72.28
The sales tax is the multiplication of the total fishing gear by 0.05
= 72.28 × 0.05
= 3.614 which is approximately 4
Amount paid by Ryan will be
Total fishing gear + Sales tax
= 72.28 + 4
= 76.28 approximately 76.
X=4
cross multiply
3x=12
x=4
Answer:
Step-by-step explanation:
The total number of ways of selecting 3 gems of any kind without replacement is 35 * 34 * 33 = 39270
Now selecting 2 gems from 25 is 25C2
25 C 2 = 25 * 24/2 = 300
Selecting one good gem is 10
Total selection = 300 * 10 = 3000
P(gems) = 3000 / 39270
P(gems) = 300/3927
P(gems) = 100/1309